La mujer en el derecho - Guerra Guerra, María Patlova (2024)
Toe move to the new condition rearranges his work ; opens new horizons and creates responsibilities not exist Toe incidence in the new state in the situation and the legal activíty of the women is a result of marriage, the lmperative that once born , there is a normative arder to resolve the difficulties and almed to achieve better way, private and not exclusive to the male and female interests, but common and social husband and wite. In the various branches o! law we see reflected the woman with their rights and obligations, being a subject of law , and commercial law , oenal law, labor law, administralíve law and political.